2010
DOI: 10.1002/hep.23743
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1b study of pegylated interferon lambda 1 with or without ribavirin in patients with chronic genotype 1 hepatitis C virus infection

Abstract: Interferon lambda 1 (IFN-k1) is a type III IFN that produces intracellular responses similar to those of IFN-a but in fewer cell types because of differences in the receptor distribution pattern, and this could potentially result in an improved safety profile. This was an open-label three-part study of patients with chronic hepatitis C virus (HCV) genotype 1 infection. Part 1 evaluated single-agent pegylated interferon lambda (PEG-IFN-k) at 1.5 or 3.0 lg/kg administered every 2 weeks or weekly for 4 weeks in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
162
0
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(166 citation statements)
references
References 25 publications
2
162
0
2
Order By: Relevance
“…37 The potential role of newer treatments (including direct-acting anti-virals and newer forms of interferon) in the treatment of chronic HCV is still being evaluated, but the data currently available for interferon-lamba 1 suggest there may be fewer neuropsychiatric complications resulting from its use compared to IFN-a. 38 Development of depression is the commonest reason for HCV treatment discontinuation. 36 A recent study found that up to 10% of patients treated for HCV with pegylated interferon and ribavirin had to prematurely withdraw from treatment, and the majority (65%) of these patients had developed features of major depression [as defined by total score >35 points on the Major Depression Inventory (MDI)].…”
Section: Depression In Patients With Chronic Liver Disease Cirrhosismentioning
confidence: 99%
“…37 The potential role of newer treatments (including direct-acting anti-virals and newer forms of interferon) in the treatment of chronic HCV is still being evaluated, but the data currently available for interferon-lamba 1 suggest there may be fewer neuropsychiatric complications resulting from its use compared to IFN-a. 38 Development of depression is the commonest reason for HCV treatment discontinuation. 36 A recent study found that up to 10% of patients treated for HCV with pegylated interferon and ribavirin had to prematurely withdraw from treatment, and the majority (65%) of these patients had developed features of major depression [as defined by total score >35 points on the Major Depression Inventory (MDI)].…”
Section: Depression In Patients With Chronic Liver Disease Cirrhosismentioning
confidence: 99%
“…Supporting this hypothesis are results from an open-label study of PEG-IFN-k1 (IL29) in patients with genotype 1 HCV, in which weekly dosing had antiviral activity and was well tolerated. 19 However, larger, blinded studies are needed to further evaluate the safety and efficacy of lambda IFNs.…”
Section: Mechanisms Of Action Of Lambda Ifns and Role Of Il28bmentioning
confidence: 99%
“…29 As described above, HCV replication is inhibited by the antiviral effects of IFN-l. A pegylated IFN-l1 has already been tried against chronic hepatitis C in phase 2 trials. 30,31 Interestingly, impressive antiviral effects (at least as good as with PegIFN-a) were observed but with fewer and less severe side effects. 31 The expression pattern of IFN-l receptor is restricted in specific tissues.…”
Section: Il-28b and Its Function Against Hcvmentioning
confidence: 99%